Synthesis, Structure and Electrochemical Performance of LiFePO4/C - Liu, Yuwen; Zhang, Wei; Jiang, Jingna (Asian Journal of Chemistry, 2016)
Olivine-type LiFePO4 and LiFePO4/C cathode materials were synthesized by hydrothermal method. The crystal structure and morphology and electrochemical performance of the materials were characterized and analyzed by X-ray diffraction, scanning electron microscopy and electrochemical testing. The effects of three different carbon sources, i.e. critic acid, poly(vinyl alcohol) and glucose, on the performance of as-synthesized cathode materials were investigated. Then, LiFePO4/C cathode materials prepared using glucose as the carbon source were modified with polyaniline (PAn) as modifier. The results show that the carbon formed from the carbon resource during hydrothermal process has obviously improved the electrochemical performance of LiFePO4, while it has no effect on the crystal structure of LiFePO4. The initial discharge specific capacity of LiFePO4/C cathode with 5 % glucose as carbon resource achieves 151.2 mAh × g-1 at 0.1 C and 87.3 mAh × g-1 at 2C, respectively. After modified by 10 % PAn the PAn0.1-LiFePO4/C0.9 delivers the capacity of 167.1 mAh × g-1 at 0.1 C and has good reversibility and high capacity retention.